Common Fixed Point Theorems in Bipolar Metric Spaces with Applications to Integral Equations - Srinuvasa Rao, B.; N.V.Kishore, G. (International Journal of Engineering and Technology, 2018)
This paper establishes the existence of coincidence fixed-point and common fixed-point results for two mappings in a complete bipolar metric spaces. Some interesting consequences of our results is achieved. Finally, an illustration which presents the applicability of the results is achieved.Â Â